MANAJEMEN HIPOTERMIA PADA PASIEN GAGAL GINJAL KRONIK PASCA HEMODIALISA DI RUMAH SAKIT TK II PUTRI HIJAU MEDAN - Rahayu, Anisyah; Jundapri, Kipa; Pratama, Muchti Yuda (EMPIRIS : Jurnal Sains, Teknologi dan Kesehatan, 2025)
Chronic kidney failure is a condition of decreased kidney function caused by the inability of the kidneys to remove metabolic waste from the body or perform their regular functions. Intervention in chronic kidney failure is performed with hemodialysis. The hemodialysis process can cause changes in body temperature to hypothermia, so it requires proper treatment. The purpose of this study is to provide an overview of the implementation of hypothermia management in patients with chronic kidney failure after hemodialysis. The research method is descriptive research with a medical-surgical nursing approach consisting of assessment, diagnosis, intervention, implementation, and evaluation. The study was conducted on two patients undergoing hemodialysis. Interventions and implementation of hypothermia management were carried out, such as monitoring body temperature, identifying the cause of hypothermia, monitoring signs and symptoms of hypothermia, providing a warm environment, changing wet clothing and/or linen, covering and applying warm compresses.The study found that body temperature returned to normal in both patients. The study concluded that monitoring body temperature, identifying the cause of hypothermia, monitoring signs and symptoms of hypothermia, providing a warm environment, changing wet clothing and/or linens, covering the patient with blankets, and applying warm compresses can help treat hypothermia in post-hemodialysis patients. This study recommends that hyperthermia management can help patients achieve normal thermoregulation, thus effectively managing hypothermia